"MAY THE SHAME BE WITH YOU. ALWAYS." MITIGATING YOUNG PEOPLE'S INTIMATE EXCHANGES ONLINE - Spišák, Sanna (AoIR Selected Papers of Internet Research, 2020)
Cultural anxiety about the impact of young people's intimate exchanges online has increased over the past 15 years. Sexual media and 'digital intimacies' are routinely understood to be a source of harm and adverse outcomes. This paper engages with Finland's National Bureau of Investigation's Sextortion video campaign, the Police of Finland's public announcements on 'teen sexting' between 2017–2019 and young Finns responses to such educational efforts by using data from Rethinking Young Finns' Practises of Mediated Intimate Exchanges study that is a part of a more significant research project on intimacy in data-driven culture in Finland. My research interest lies with some of the disconnections between current educational and policy discourses addressing young people's participation in digital cultures, and the lived experiences of young Finns. By asking from a focus-group of young Finns aged 15–19-years-old how they and their peers experience digital intimacy and their perceptions of the benefits, possible risks and harms, mitigations and solutions, I can draw a more ethical yet a complex picture of young people's engagement with digital intimacies. I call for a focus on the political, ethical and material implications of such educational efforts and policy responses that premises on digital abstinence to critically reflect on the question of young people's (sexual) rights in digital environments. The University of Turku ethics board has approved the research design and the uses of all the research datasets.